Optimalisasi Pemasaran Digital Dan Pendaftaran Hak Merek Pada UMKM Batik Menuju Dayasaing Global - Sunarjo, Wenti Ayu; Wibowo, Dwi Edi; Nasution, Nur Baiti; Rabbani, Nauval; Sasongko, Aditya Dimas Wahyu (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2024)
Community service activity partners are a group of productive partners, namely batik MSMEs in Pekalongan City, namely those who are members of the Kauman batik kampoeng association and the Pesindon batik tourism village. The main problem is marketing, especially digital product marketing in improving the brand image of batik MSMEs towards global competitiveness. This is in line with the aim of community service to optimize digital marketing for batik MSMEs to be able to increase global competitiveness through digital marketing training and mentoring activities by utilizing social media and e-commerce platforms and brand rights registration as part of MSME branding and functions so that consumers can characterizes a product owned by batik MSMEs so that it can differentiate it from other batik products. This activity is divided into three stages, namely the preparation stage including identifying each partner's problem and preparing a problem solving plan, the implementation stage in the form of introducing digital marketing strategies as well as training on marketing utilization and optimization as well as introduction and assistance in creating brand rights, the conclusion evaluation stage of the entire activity, suggestions and conclusions from the results of community service activities. The results obtained from this activity are that batik MSMEs are still minimal in optimizing digitalization for marketing their products, as well as brand rights, only 20% of batik MSMEs have trademarks, the rest have no awareness of trademarks and don't even want to officially register their danang brands.